Enhancement of gas turbine power output using earth to air heat exchanger (EAHE) cooling system. (1st March 2016) - Barakat, S.; Ramzy, Ahmed; Hamed, A.M.; El Emam, S.H.
Highlights: Earth to air heat exchanger as an inlet air cooling system on gas turbine is investigated. Gas turbine output power, efficiency and specific fuel consumption are assessed. Output power production as well as the thermal efficiency by 9% and 4.8%, respectively. The annual revenue increases by 1.655 ∗ 10 6 with payback period of 1.2 year. Abstract: The application of earth to air heat exchanger (EAHE) as an inlet air cooling system on gas turbine performance has been investigated. Transient, one-dimensional model was developed for predicting the thermal performance of EAHE. Gas turbine output power, efficiency and specific fuel consumption are assessed with application of EAHE. MATLAB program is developed for solving the discrete numerical equations. Damietta power plant is selected as case study. The output power and thermal efficiency of gas turbine increases by 9% and 4.8%; respectively. In addition the annual revenue will increase by 1.655 ∗ 10 6 with payback period of 1.2 year.